The Data-Its Adequacy and Accuracy in Presentation; Probability, Dispersion and the Correlation (Statistical Applications in Medical Research) - Kumar, Ashok (Journal of Universal College of Medical Sciences, 2013)
The data forms the main base at the very grass root level and is the BACK BONE for application of all the statistical methods, be it in the field of medical sciences, social sciences or any such allied field. The present paper, in this direction, attempts to HIGHLIGHT the main considerations and points to be taken care of in DATA ANALYSIS, towards statistical Inference(s) DOI: http://dx.doi.org/10.3126/jucms.v1i2.8414 Journal of Universal College of Medical Sciences Vol.1(2) 2013: 69-74